CESifo World Economic Survey November 2006 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2006)
World Economic Climate: Soft-landing is likely - Economic Expectations: Assessments of the current economic situation continue to improve, economic expectations somewhat downgraded - Inflation: Expectations: Only moderate further increase - Interest Rates: Upward trend is slowing down - Currencies: Japanese yen still seen as somewhat undervalued - Special Topic: The suspension of the WTO trade negotiations
Keywords: 330